Parental Self-Medication with Antibiotics in Pakistan - Abdul Salam, Samina Waseem, Laiba Akhtar, Hafiz Abdul Manan, Muhammad Awais Bin Abdul Malik, Noman Siddique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Antibiotic resistance due to irrational use of antibiotics is on an alarming level and self-medication is a key factor behind this. Self-medication refers to the use of medicines to treat self-diagnosed disease. Parent’s knowledge and behavior is an important factor to reduce practice of self-medication. This study aims to evaluate prevalence of parental self-medication with antibiotics and knowledge, attitude and practices toward antibiotics use. Methods: A cross-sectional descriptive statistical analysis was performed which targeted parents of children between ages 1-14 by self-administered questionnaire. Results: Responses showed that 81.9% of participants had knowledge about antibiotics and among this percentage 21.8% did not visit physician and self-medicated their child in case of disease. Of those who had visited physician in case of disease, 50.8% refilled last prescription in case of recurrence of disease. Study showed there is a significant relationship between parent’s education and physician visit. Only 15.2% of participants had good knowledge about antibiotics resistance. Practical Implication: Adults in Pakistan have been documented as engaging in antibiotic self-medication. However, there is scant data on parents who medicate their kids at home. To the best of our knowledge, however, there has been no research done on the prevalence of self-medication among the people of Punjab. Conclusion: Parent’s awareness and health education are the main contributing factors in proper use of antibiotics and should be considered by health policy makers. Antibiotics stewardship programs must be tailored in favor of parent’s awareness about antibiotics use. Keywords: Self-medication, Antibiotics, Parents education, Children, Pakistan